An Experimental Investigation On The Performance Of The Modified Connection Of Overhang Roof Steel Cladding Subjected To Static Load - Abdullah, Fatin Huwaina (Universiti Sains Malaysia, 2021)
The study of effects on wind loading to the roof cladding and purlin connection become the focus of the present study. It is found that the failure of roof cladding initiated at the overhang roof due to turbulence created form the strong wind. However, the previous studies are limited to the non-engineered building without overhang roof mainly the rural house in northern region of Peninsular Malaysia. In this study, the typical overhang roof length was obtained through rural house survey. The experimental study using simple pull-through, and pull-out test was performed to simulate the wind loading effect on rural house features especially at overhang roof. Therefore, the study is conducted to investigate the pull-through and pull-out capacity on cladding to purlin connection of rural house. The tests were conducted on two types of claddings namely, corrugated and trapezoidal roof cladding. The purlin used timber type Dark Red Meranti which classified under strength group 6 and the wind loading was applied via hydraulic jack machine. In the experimental work, two different thickness of cladding is used, which is 0.18 mm for corrugated steel cladding and 0.23 mm for trapezoidal steel cladding. The specimen is built with different types of assembly, namely control sample, modification 1, with the addition of roof cladding strap and modification 2, with the addition of roof cladding strap and small size wood. Based on the result from the experimental work, it can be identified that both specimen in modification 1 and 2 are having higher value of maximum load cell nail, 2.10 kN and 2.304 kN compared to 0.94 kN and 1.138 kN from control sample and maximum applied load, 4.91 kN and 6.367 kN compared to 2.74 kN and 2.804 kN from control sample for corrugated and trapezoidal roof cladding. Therefore, it can be concluded that the modification in the roof connection can increase its strength.